A Comparative Analysis of Extracted Human Teeth Sterilization by Using Distinctive Sterilizing Agents - Nishant; Sharma, Bhagwat S.; Chandel, Shilpi Singh; Rajput, Neha (Journal of College of Medical Sciences-Nepal, 2024)
Background Regular use for practice and educational purposes of Extracted human teeth in dental institutions at undergraduate and postgraduate levels is a necessity. Individuals who collect extracted teeth must decontaminate and then handle teeth. Different materials and methods are used for sterilizing extracted teeth to avoid infection from them. Methods Total of 50 freshly extracted human teeth that were intact, non-carious and extracted due to periodontal disease or orthodontic purpose were divided randomly into 5 groups consisting of 10 teeth in each group.These were stored in sterile saline till tested and will randomly be divided into one of the following 5 groups of sterilizing agents consisting of 5.25% sodium hypochlorite, 10% formalin, 2% glutaraldehyde, Microwave Radiation and a control group with normal saline. All teeth will be immersed in separate bottles. Samples were collected with the help of inoculating loop and then streaked over the surface of Mc-conkey agar medium. The media was incubated at 37 degree C for 24 h. Sterilization was determined based on the growth of micro-organisms on culture medium. Evidence of growth was observed after 24 hour of inoculation. Absence of any visible growth in the media was the indicator of an effective sterilization. Results This research showed that, 10% formalin, 5.25% sodium hypochlorite could be efficiently used for sterilization and disinfectionof extracted human teeth. Conclusions Extracted teeth are potential source of infection hence should be disinfected before any use in the laboratories.